Current Status Of Rainfed Land Use In The Republic Of Uzbekistan (Eurasian Journal of Engineering and Technology, 2025)
This article analyzes the current state of rainfed land use in the Republic of Uzbekistan, including the regional distribution of rainfed areas, soil bonitet scores, the degree of land degradation, and their economic efficiency. The study employs statistical data, cartographic analysis, and economic valuation methods based on normative land value. The results show that the efficiency of rainfed land use remains insufficient, with declining soil productivity and a high risk of erosion. The article concludes with recommendations for ensuring sustainable use of rainfed land resources.